Low Concentrations of Monosodium Glutamate (MSG) are Safe in Male Drosophila Melanogaster. - Keneth Iceland, Kasozi; Namubiru, Sarah; Kiconco, Oliver; Kinyi, Hellen Wambui; Ssempijja, Fred; Chukwujekwu Ezeonwumelu, Joseph Obiezu; Ninsiima, Herbert Izo; Okpanachi, Alfred Omachonu (Kabale University, 2023)
Objective: Monosodium glutamate (MSG) has been marred by a lot of controversy on its safety. In a majority of experimental studies, administration of the compound has been parenteral, and yet little is known about MSG safety consumed as a food supplement. In this study, we assessed the effects of low concentrations of MSG on the activity of hydrogen scavenging, catalase activity and climbing as well as lifespan in male Drosophila melanogaster over a 30 days period since this has been sparsely studied. Results: No significant differences were associated with MSG at 5%, 1%, 0.2%, 0.04% on hydrogen peroxide scavenging,negative geotaxis and lifespan in W1118 male D. melanogaster. Significant differences were found in 5% MSG on catalase activity, showing that high MSG concentrations would affect tissue health in male D. melanogaster. MSG consumed as a food supplement would be safe at concentrations below 5% MSG. Keywords: Drosophila Melanogaster, MSG Safety, MSG Toxicity, Catalase Activity.